Fluorescent Cadmium Chalcogenide Nanoclusters in Ubiquitin. Issue 2 (11th February 2021) - Akyüz, Özlem; Scheffner, Martin; Cölfen, Helmut
Abstract : Fluorescent Nanoclusters Cover image represents the fluorescent cadmium chalcogenide nanoclusters (CdNCs) synthesized in ubiquitin (Ub) under mild reaction conditions. The results indicate that even a small cysteine‐free protein, namely Ub, has the ability to be used in fluorescent CdNCs stabilization by forming oligomeric and hydrated species. More details can be found in article number 2000127 by Helmut Cölfen and co‐workers.